Pengaruh lama pemasakan daging anjing terhadap sifat mutu organoleptik - Lahiwu, J.; Rompis, J.E.G.; Surtijono, S.E.; Tinangon, M.R. (ZOOTEC, 2021)
THE EFFECT OF THE DURATION OF COOKING DOG MEAT ON ORGANOLEPTIC QUALITY PROPERTIES. The purpose of this study was to determine the effect of cooking time on dog meat on its organoleptic qualities. The ingredients used were male dog meat aged 14 months, The meat dog was taken from the thigh as much as 3 kg and spices, four treatments were tested in this study, namely, P1: 60 minutes of cooking, P2: 80 minutes of cooking, P3: 100 minutes of cooking, P4: 120 minutes of cooking. This experiment used a completely randomized design (CRD) and was assessed by 40 panelists to determine the organoleptic properties of the cooking time dog meat. Measurement of organoleptic data using a hedonic scale consisting of variables of color, aroma, tenderness, texture, teste, to determine differences in treatment was carried out by the DMRT test. The results of this study indicated that the treatment had a very significant effect (P<0,01) on the color, aroma, tenderness, texture, and taste of dog meat- the condusion is based on the organoleptic quality characteristics, overall cooking time of dog meat is acceptable, but cooking time of 120 minutes is preferred and accepted by the panelists.Keywords: Cooking time, Dog meat, Organoleptic